Kemampuan Berpikir Kreatif Mahasiswa Pendidikan Biologi dalam Penyelesaian Masalah Ekologi Hewan - Riyadi, Agus Setiawan; Dharmono, Dharmono; Naparin, Akhmad; Zaini, Muhammad (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2018)
Creative thinking is one of the important competencies as part of the life skills that become one of the national educational purposes. Every individual needs the creative thinking ability to solve problems in life. It is because with creative thinking, individuals can be trained to solve problems in different ways and diverse. Giving problems to be solved by the student’s can trace the creative thinking ability as well, because to solve a problem, one must have the creative thinking ability. The purpose of this research was to describe the student’s creative thinking ability Program Biology Education of Lambung Mangkurat University in problem solving of animal ecology. Type of this descriptive research with a quantitative approach. Population in this research is all student’s Biology Education of Lambung Mangkurat University who have taken animal ecology course in academic year 2015/2016 which amounted to 82 people, with a sample 30% of the population, that is 30 students taken from three categories high, medium and low based on the value of animal ecology course. The data generated in this research were analyzed using data analysis techniques descriptive quantitative. Quantitative data obtained from the results of the assessment of student answers to the question of written assignment that will be analyzed in percentage, then converted into descriptive data according to the category based on the percentage obtained. The results of this research indicate that the level of creative thinking ability student’s Biology Education of Lambung Mangkurat University dominant at the level of quite creative.